Globalization, society and environmental management challenges in the 21st century - Jamaluddin Md. Jahi (Environmental Management Society, Malaysia, 2003)
Ever since people utilize resources, environmental quality started to deteriorate. Throughout history we have heard of, through space and time, human activities impacting on the environment that resulted in environmental degradation. Globalization leads to greater trading and utilization of natural resources. The principles of sustainable development were introduced, during the last quarter of the 20th century, as measures to look after our earth as a result of increasing environmental problems where some have reached global proportion. It is imperative that development is required for progress and one way of dealing with possible environmental problems is to consider environment in any economic activity. As such, globalization which leads to grater trading of goods and nature-based products has to be constantly monitored through policies and strategies. Various incidences of environmental quality deterioration had resulted in increased awareness, which led to the formulation of the concept of sustainable development. The underlying principles have become added challenges to countries around the world in managing the environment, especially when globalization has in directly ‘created’ global environmental problems that requires clear-cut policies and integrated approaches by poor and rich countries alike